Basic Study on Navigation Aid System when Pilot Trainee Crosses Sea Route - Okazaki, T.; Shigeta, S.; Kato, T. (2012 Fifth International Conference on Emerging Trends in Engineering and Technology, 2012)
This study aimed to improve the navigation skill of third grade pilot trainee in ship simulator training. In this study, navigation aid system when the pilot trainee crossed sea route in the ship simulator training was developed. The effectiveness of developed system was showed with the simulator experimental results.